Central African Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper examines the underlying causes of the Central African Republic's 'fragility trap' and sheds light on factors linked to building resilience. The persist fragility in the Central African Republic can be attributed to several factors: lack of political cohesion and state weakness that led to protracted political crises and conflicts, weak capacity and poor commitment to building economic institutions, and the inability to generate or appropriately use fiscal buffers. The findings underscore the need for promoting peaceful and inclusive societies; strong international support; and building effective, accountable, and inclusive institutions-especially fiscal institutions-as a foundation for building resilience in the Central African Republic's exit from fragility.